Prevalence of risk factors for development of cardiovascular diseases in urban and rural areas of Eastern Croatia: a cross-sectional study - Klapec-Basar, Mirta; Kovač, Tanja; Apatić, Renata; Mudri, Željko; Basar, Tin; Jurić, Stjepan; Gmajnić, Rudika; Lovrić, Robert (Central European journal of public health, 2024)
OBJECTIVE: Cardiovascular diseases are the leading global cause of death. Due to the disparities in cardiovascular risk factors between rural and urban populations, this study aims to assess the differences in the prevalence of risk factors in urban and rural areas of eastern Croatia. METHODS: The cross-sectional study included 280 participants (140 from urban and 140 from rural areas) registered at studied general practice offices. Methods included e-health records, questionnaire, physical examination methods, and blood sampling for laboratory tests. RESULTS: The most common risk factors among participants were elevated total cholesterol (83.6%), elevated LDL cholesterol (81.8%), increased body mass index (75.0%), increased waist-hip ratio (82.9%), increased waist circumference (63.2%), and arterial hypertension (70.1%). The rural participants had a significantly higher prevalence of arterial hypertension (p = 0.023), increased body mass index (p = 0.004), increased waist circumference (p = 0.004), increased waist-hip ratio (p < 0.001), and increased LDL cholesterol (p = 0.029), while the urban participants had a significantly higher prevalence of insufficient physical activity (p < 0.001). CONCLUSIONS: In the examined sample, the prevalence of cardiovascular risk factors is generally high. Participants from rural areas are significantly more susceptible to cardiovascular risk factors than participants from urban areas.
Keywords: index tělesné hmotnosti; senioři; Waist-Hip Ratio; Cross-Sectional Studies; Prevalence; risk factors; Croatia; rural population; Middle Aged; průzkumy a dotazníky; mužské pohlaví; prevalence; průřezové studie; Adult; Chorvatsko; urban population; Body Mass Index; Heart Disease Risk Factors; Cardiovascular Diseases; venkovské obyvatelstvo; městské obyvatelstvo; ženské pohlaví; Humans; Surveys and Questionnaires; lidé středního věku; Rural Population; rizikové faktory; cardiovascular disease; dospělí; Urban Population; rizikové faktory kardiovaskulárních chorob; Female; Risk Factors; poměr pasu a boků; Aged; kardiovaskulární nemoci; lidé; Male